New organic precursors for carbon material : precursor development and carbonization process - Tay, Yu Shan (Nanyang Technological University, 2021)
Carbon materials possess properties such as being light weight, having high strength, thermal and electrical conductivity etc. which made them highly sought after for many applications. Polyacrylonitrile (PAN) is one of the few organic precursors with a relatively high char yield and an organised structure after carbonization. Phthalonitrile-based carbon materials are usually high temperature resistant with intrinsic porosity. As research progresses, many more carbon precursors have been discovered. However, each carbon precursor has its own advantages and disadvantages. For example, PAN can retain structure after carbonization with proper oxidative stabilization step but has a low char yield compared to resorcinol-based phthalonitrile (rPN). On the other hand, rPN has a high char yield but tedious curing procedure and its physical structure is not maintained after carbonization as it melts during curing. It would be ideal to combine the advantages of two good carbon precursors and at the same time solve the problems arising from using individual precursors alone, in order to produce better carbon materials. This study belongs to ongoing research efforts to develop new precursors for carbon materials with enhanced properties.